(untitled) (Jurnal Teknologi (Sciences & Engineering), 2024)
Many hardening methods have been developed and proposed as an effective technology to produce microstructural modification and improvement of mechanical properties of variety metallic materials. In this experimental study, the effects of applying laser peening (LP) and friction stir processing (FSP) methods on wear resistance and fatigue properties of selected cast iron ASTM A536, grade (80-55-06) with ferrite/pearlite microstructure were investigated. Microscopic study revealed evident refinement and crashing of graphite nodules as 50% of the basic size with FSP and 32% with LP within the processed surfaces hence improving average microhardness by 100% and 48% respectively. The wear resistance and fatigue life were increased by 33% and 122% after FSP whereas, the corresponding increments were 15% and 22% after LP in comparison with the basic ductile iron. These improvements were linked to surface hardening, compressive stresses and structural modification by the employed processes.